2018
DOI: 10.1038/s41598-018-20668-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Translation of Tethered Confocal Microscopy Capsule for Unsedated Diagnosis of Eosinophilic Esophagitis

Abstract: Esophagogastroduodenoscopy (EGD) is a widely used procedure, posing significant financial burden on both healthcare systems and patients. Moreover, EGD is time consuming, sometimes difficult to tolerate, and suffers from an imperfect diagnostic yield as the limited number of collected biopsies does not represent the whole organ. In this paper, we report on technological and clinical feasibility of a swallowable tethered endomicroscopy capsule, which is administered without sedation, to image large regions of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…6a) covered a 20-cm length of the esophagus and stomach. 61.4% of the SECM imaging area had contact with the tissue, which was similar to the tissue contact proportion measured with the longer SECM capsule, 66.5% [15]. Imaging time was 30 seconds.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…6a) covered a 20-cm length of the esophagus and stomach. 61.4% of the SECM imaging area had contact with the tissue, which was similar to the tissue contact proportion measured with the longer SECM capsule, 66.5% [15]. Imaging time was 30 seconds.…”
Section: Resultssupporting
confidence: 71%
“…Both images were normalized with the same intensity threshold. A magnified view of the Figure 8a Figure 8b shows a bi-lobed cell nucleus (arrow) without a surrounding dark background, suggestive of an eosinophil [15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41,59,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Swallowable, capsulebased OCT probes have also been developed for upper GI imaging without the need for sedation or traditional white light endoscopy. [76][77][78][79][80] Higher-resolution forms of OCT are also under development and have achieved resolutions of 1 lm in the ex vivo setting. [81][82][83][84] Confocal microscopy is an optical imaging technique that typically uses a pinpoint beam of light scanned across a tissue to create an en face, or transverse, image.…”
Section: Optical Imaging Modalitiesmentioning
confidence: 99%
“…and submucosal structures of the oesophagus in microscopic detail (axial resolution: ~10 µm, lateral resolution: 13 ~30µm) and has been successfully demonstrated in ex vivo and in vivo trials 91,98,170,171 . Various studies using OCT 14 with conventional endoscopy have demonstrated high-resolution volumetric images comparable to those obtained 15 from histology.…”
mentioning
confidence: 99%